Long-term changes in red tide outbreaks in Xiamen Bay in China from 1986 to 2017. (5th February 2021) - Baohong, Chen; Kang, Wang; Xu, Dong; Hui, Lin
Abstract: Data on red tide (harmful algae blooms, HABs) from 1986 to 2017 in Xiamen Bay of Fujian province in China was collected. In these 30 years, a total of 53 red tide events were recorded, which mostly happened in West sea (47.3%) and Tong'an Bay (40.5%). And, red tide areas in Xiamen Bay have expanded, with the most prone area changing from West sea to Tong'an Bay. Furthermore, red tide focused on late spring and summer, including the months of May, June and July, with the percentage of occurrence of 13.8%, 26.2% and 27.7%, respectively. By contrast, red tide seldom occurred in autumn. Skeletonema costatum, Chaetoceros curvisetus and Akashiwo sanguinea were dominant red tide species in the bay responsible for red tide events on 24, 8 and 6 occasions so far, respectively. Red tide events caused by Dinoflagellates have been increasing in these 30 years. While red tide events caused by Diatom decreased in 2010s obviously compared to those in 2000s. It was suggested that changes of eutrophication degree and nutrient ratios, climate change, and sediment property maybe important factors to the long-term changes in red tide outbreaks in Xiamen Bay. Highlights: 1. Trends of red tide in a subtropical bay of China were studied. 2. Dominant red tide species have changed from diatom to dinoflagellate. 3. Akashiwo sanguinea blooms always break out at the same site in the Bay. 4. Eutrophication and climate change were important reasons for the changes.